News construction bases on multicultural values at TVRI Samarinda Station in the digital era - Sudono, Sudono; Basirun; Siti Asiatun (Program Pascasarjana Universitas Negeri Yogyakarta, 2025)
This study examines the principles of news content based on multicultural values at TVRI Samarinda Station through a framing analysis approach. As a public broadcasting institution, TVRI Samarinda plays a pivotal role in promoting national identity and cultural diversity while facing challenges related to human resource development and technological adaptation. Drawing on news construction theory and framing theory, this research explores how news content broadcast by TVRI Samarinda constructs and reflects multicultural values within society. The study employs a qualitative research method with a constructivist approach. Data were collected through in-depth interviews with key stakeholders at TVRI Samarinda Station, including the Station Director and the Head of the News Division. The findings reveal that the news scripts broadcast by TVRI Samarinda have successfully addressed multicultural issues, although the newsroom team still requires a deeper understanding of socio-cultural dynamics. TVRI Samarinda has demonstrated its capacity to maintain social harmony in East Kalimantan as a media entity with the mandate to foster national unity. Consequently, TVRI Samarinda plays a significant role in preserving social cohesion and fostering awareness of cultural diversity within the community. This paper contributes by revealing how TVRI Samarinda constructs and promotes multicultural values through its news framing, thereby strengthening social cohesion and enhancing the role of public broadcasting in a culturally diverse society.